Symbol

# Calculator search results

Formula
Solve the equation
Graph
$y = - 2 x - 3 \left ( 3 x + 5 \right )$
$y = 7$
$x$Intercept
$\left ( - \dfrac { 15 } { 11 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 15 \right )$
$-2x-3 \left( 3x+5 \right) = 7$
$x = - 2$
 Solve a solution to $x$
$- 2 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) = 7$
 Multiply each term in parentheses by $- 3$
$- 2 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = 7$
$- 2 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 3 } \color{#FF6800}{ x } - 3 \times 5 = 7$
 Simplify the expression 
$- 2 x \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ x } - 3 \times 5 = 7$
$- 2 x - 9 x \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ \times } \color{#FF6800}{ 5 } = 7$
 Multiply $- 3$ and $5$
$- 2 x - 9 x \color{#FF6800}{ - } \color{#FF6800}{ 15 } = 7$
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 9 } \color{#FF6800}{ x } - 15 = 7$
 Calculate between similar terms 
$\color{#FF6800}{ - } \color{#FF6800}{ 11 } \color{#FF6800}{ x } - 15 = 7$
$- 11 x \color{#FF6800}{ - } \color{#FF6800}{ 15 } = 7$
 Move the constant to the right side and change the sign 
$- 11 x = 7 \color{#FF6800}{ + } \color{#FF6800}{ 15 }$
$- 11 x = \color{#FF6800}{ 7 } \color{#FF6800}{ + } \color{#FF6800}{ 15 }$
 Add $7$ and $15$
$- 11 x = \color{#FF6800}{ 22 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 11 } \color{#FF6800}{ x } = \color{#FF6800}{ 22 }$
 Change the sign of both sides of the equation 
$11 x = - 22$
$\color{#FF6800}{ 11 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 22 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$x = - 2$
Solve the fractional equation
$\color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 } \right ) = \color{#FF6800}{ 7 }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture